THEIR CLINICAL SIGNS AND BLOOD MORPHOLOGICAL INDICATIONS IN THE TREATMENT OF ASEPTIC PODODERMATITIS IN COWS (Conferencea, 2024)
In the article, in livestock farms specializing in dairy farming in our Republic, purebred cows have their hooves cleaned and trimmed, then bathed in 5% formalin, hydrocortisone 4ml, 0.5% novocaine 5ml intramuscularly, cal-bor-mag (250 ml intravenously every 24 hours times in total three times), phenylbutazone-20 (5 ml intravenously for 100 kg body weight once every 48 hours for a total of three times) reduced inflammatory processes, increased regeneration processes and increased the number of erythrocytes in the blood by 18.4%, the amount of hemoglobin It is reported to increase by 8.5%, decrease the number of leukocytes by 15.8%, and decrease the erythrocyte sedimentation rate by 27.2%.